2022
DOI: 10.21608/ejcm.2022.130974.1212
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of health belief model-based educational intervention in improving knowledge, beliefs, smoking behaviors, and nicotine dependence among cigarette smoking medical students during COVID-19 pandemic

Abstract: Background: Cigarette smoking is a major public health threat to the world with rising concerns during the COVID-19 pandemic. Objectives: To evaluate the effectiveness of a health belief model (HBM)-based educational intervention in improving knowledge, beliefs, selfreported smoking behaviors, and nicotine dependence among university medical students. Method: A randomized intervention was performed using permuted blocks randomization. Students in the intervention group (n=133) received health education interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…The findings showed that the HBM questionnaires had a significant impact on the post-test for the experimental group. This outcome was in line with the findings of Tawfik, Soliman, and Elotla (2022), who reported that following the intervention, the percentage of students who had high scores on knowledge and belief tests significantly increased compared to the control group. Furthermore, Pribadi and Devy (2020) discovered that there was a substantial association between the intention of young adult smokers to quit smoking and the perceived factors of the HBM.…”
Section: Health Belief Model Constructs Along With Health Education T...supporting
confidence: 90%
“…The findings showed that the HBM questionnaires had a significant impact on the post-test for the experimental group. This outcome was in line with the findings of Tawfik, Soliman, and Elotla (2022), who reported that following the intervention, the percentage of students who had high scores on knowledge and belief tests significantly increased compared to the control group. Furthermore, Pribadi and Devy (2020) discovered that there was a substantial association between the intention of young adult smokers to quit smoking and the perceived factors of the HBM.…”
Section: Health Belief Model Constructs Along With Health Education T...supporting
confidence: 90%